Diagnostic x-ray dosimeters using standard float zone (FZ) and XRA-50 commercial diodes - Josemary A. C. Gonçalves; Vinicius S. M. Barros; Viviane K. Asfora; Helen J. Khoury; Carmen C. Bueno (Brazilian Journal of Radiation Sciences, 2019)
The results obtained with a standard float zone (FZ) silicon diode, processed at the Helsinki Institute of Physics, used as on-line diagnostic X-ray dosimeter are described in this work. The device was connected in the short-circuit current mode to the input of an integrating electrometer. The response repeatability and the current sensitivity coefficient of the diode were measured with diagnostic X-ray beams in the range of 40-80 kV. The dose-response of the device, evaluated from 10 mGy up to 500 mGy, was linear with high charge sensitivity. Nevertheless, significant energy dependence was observed in the charge sensitivity of FZ device for energies below 70 kV. The dosimetric characteristics of this FZ diode were compared to those of an XRA-50 commercial Si diode, specially designed to X-ray dosimetry. The results obtained with the  FZ diode evidenced that it can be an alternative choice for diagnostic X-ray dosimetry, although it needs to be calibrated for individual X-ray beam energies. The studies of long-term stability and the radiation hardness of these diodes are under way.